Amantadine to Treat Cognitive Dysfunction in Moderate to Severe Traumatic Brain Injury. Issue 4 (July 2015) - Stelmaschuk, Stephanie; Will, Mary Colleen; Meyers, Tamara
Abstract : Traumatic brain injury (TBI) is a leading cause of injury, disability, and death in the United States. Amantadine is an established dopamine agonist that supports neurological function. The purpose of this literature review was to determine whether amantadine improves cognitive function post-TBI. PubMed and CINAHL were used to search the literature for articles using amantadine to treat TBI from 1994 to 2004. Outcomes were summarized and the evidence was appraised. Although earlier studies from 1994 to 2003 were lower-level studies and recommended further research on treatment of cognitive dysfunction in TBI, the literature from 2004 to present generally concluded that amantadine improved cognitive function related to arousal, memory, and aggression. It can be started days to months postinjury and still produces benefits.